Optimization of wear and cracks in roller contact under different coating and a range of loads and temperature with fixed speed using design expert (DOE) and finite element model - Nehme, Gabi; Al Esber, Monzer (International Journal of Engineering and Technology, 2022)
Superior coating technology and roller materials such as M50 steels (0.8C–4.2Cr–4.3Mo–1V wt. %) and (1.0C–2.0Cr–0.5Mo–1.0Mn– 0.5Si wt. %) are well recognized in modern technology. The aim is to present all the external and internal parameters that affect the rolling system by taking into consideration the microstructure importance in identifying the service life of such rolling technique. The most dangerous defects are the cracks and wear under high loading contact and temperature formed during the rolling process.Finite elements method was used to simulate rolling and to calculate the extensive wear in order to use DOE to optimize several conditions from coating to load and temperature. The analysis involved here used the steel rollers with and without coatings, which include titanium nitride (TiN), zirconium nitride (ZrN), and tungsten carbide (WC) under different temperature and loading conditions. Results showed that cracks propagation were limited to extreme load when using coating technology. Design Expert optimization confirmed that TiN and WC coatings would enhance the lifetime of rollers and inhibit cracks initiations and extensive wear that could results in severe plastic deformation.